Question
upstudy study bank question image url

AP Calculus AB L'Hospital's Rule Worksheet Evaluate the limits: 1. \( \lim _{x \rightarrow 4} \frac{3 x-12}{x^{2}-16} \) 2. \( \lim _{x \rightarrow-4} \frac{2 x^{2}+13 x+20}{x+4} \) 3. \( \lim _{x \rightarrow 6} \frac{\sqrt{x+10}-4}{x-6} \) 4. \( \lim _{x \rightarrow 0} \frac{\sin 6 x}{4 x} \) 5. \( \lim _{x \rightarrow 3} \frac{x^{2}-2 x-3}{x-3} \) 6. \( \lim _{x \rightarrow 0} \frac{\sqrt{25-x^{2}}-5}{x} \) 7. \( \lim _{x \rightarrow 0} \frac{\sin 3 x}{\sin 5 x} \) 8. \( \lim _{h \rightarrow 0} \frac{\sin (x+h)-\sin x}{h} \) 9. \( \lim _{x \rightarrow \infty} \frac{5 x^{2}+3 x-1}{4 x^{2}+5} \) 10. \( \lim _{x \rightarrow 0} \frac{\sin ^{2} 2 x}{5 x^{2}} \) 11. \( \lim _{x \rightarrow 0} \frac{\sin 5 x}{\tan 9 x} \) 12. \( \lim _{x \rightarrow 5} \frac{\sqrt{x+4}-3}{\sqrt{x-1}-2} \) 13. \( \lim _{x \rightarrow \frac{\pi}{3}} \frac{\cos x-\frac{1}{2}}{x-\frac{\pi}{3}} \) 14. \( \lim _{x \rightarrow 3} \frac{\frac{1}{x}-\frac{1}{3}}{x^{2}-9} \) 15. \( \lim _{x \rightarrow 2} \frac{x^{2}-4 x+4}{x^{2}-x-2} \)

Ask by Herrera Frank. in the United States
Feb 28,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( \frac{3}{8} \) 2. \( -3 \) 3. \( \frac{1}{8} \) 4. \( \frac{3}{2} \) 5. \( 4 \) 6. \( 0 \) 7. \( \frac{3}{5} \) 8. \( \cos x \) 9. \( \frac{5}{4} \) 10. \( \frac{2}{5} \) 11. \( \frac{5}{9} \) 12. \( \frac{2}{\sqrt{5}} \) 13. \( \cos\left(\frac{\pi}{3}\right) \)

Solution

Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-2x-3=0\) - step1: Factor the expression: \(\left(x-3\right)\left(x+1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-3=0\\&x+1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=3\\&x=-1\end{align}\) - step4: Rewrite: \(x_{1}=-1,x_{2}=3\) Solve the equation \( \frac{x^{2}-4x+4}{x^{2}-x-2}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x^{2}-4x+4}{x^{2}-x-2}=0\) - step1: Find the domain: \(\frac{x^{2}-4x+4}{x^{2}-x-2}=0,x \in \left(-\infty,-1\right)\cup \left(-1,2\right)\cup \left(2,+\infty\right)\) - step2: Divide the terms: \(\frac{x-2}{x+1}=0\) - step3: Cross multiply: \(x-2=\left(x+1\right)\times 0\) - step4: Simplify the equation: \(x-2=0\) - step5: Move the constant to the right side: \(x=0+2\) - step6: Remove 0: \(x=2\) - step7: Check if the solution is in the defined range: \(x=2,x \in \left(-\infty,-1\right)\cup \left(-1,2\right)\cup \left(2,+\infty\right)\) - step8: Find the intersection: \(x \in \varnothing \) Solve the equation \( 2x^{2}+13x+20=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(2x^{2}+13x+20=0\) - step1: Factor the expression: \(\left(x+4\right)\left(2x+5\right)=0\) - step2: Separate into possible cases: \(\begin{align}&2x+5=0\\&x+4=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=-\frac{5}{2}\\&x=-4\end{align}\) - step4: Rewrite: \(x_{1}=-4,x_{2}=-\frac{5}{2}\) Solve the equation \( \frac{\sin^{2}(2x)}{5x^{2}}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sin^{2}\left(2x\right)}{5x^{2}}=0\) - step1: Find the domain: \(\frac{\sin^{2}\left(2x\right)}{5x^{2}}=0,x\neq 0\) - step2: Cross multiply: \(\sin^{2}\left(2x\right)=5x^{2}\times 0\) - step3: Simplify the equation: \(\sin^{2}\left(2x\right)=0\) - step4: Set the base equal to 0: \(\sin\left(2x\right)=0\) - step5: Use the inverse trigonometric function: \(2x=\arcsin\left(0\right)\) - step6: Calculate: \(2x=0\) - step7: Add the period: \(2x=k\pi ,k \in \mathbb{Z}\) - step8: Solve the equation: \(x=\frac{k\pi }{2},k \in \mathbb{Z}\) - step9: Check if the solution is in the defined range: \(x=\frac{k\pi }{2},k \in \mathbb{Z},x\neq 0\) - step10: Find the intersection: \(x=\frac{k\pi }{2},k \in \left(-\infty,0\right),k \in \mathbb{Z}\cup k \in \left(0,+\infty\right),k \in \mathbb{Z}\) Solve the equation \( \frac{\sqrt(25-x^{2})-5}{x}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sqrt{25-x^{2}}-5}{x}=0\) - step1: Find the domain: \(\frac{\sqrt{25-x^{2}}-5}{x}=0,x \in \left[-5,0\right)\cup \left(0,5\right]\) - step2: Cross multiply: \(\sqrt{25-x^{2}}-5=x\times 0\) - step3: Simplify the equation: \(\sqrt{25-x^{2}}-5=0\) - step4: Move the constant to the right-hand side: \(\sqrt{25-x^{2}}=5\) - step5: Raise both sides to the \(2\)-th power\(:\) \(\left(\sqrt{25-x^{2}}\right)^{2}=5^{2}\) - step6: Evaluate the power: \(25-x^{2}=25\) - step7: Move the constant to the right side: \(-x^{2}=25-25\) - step8: Subtract the terms: \(-x^{2}=0\) - step9: Change the signs: \(x^{2}=0\) - step10: Set the base equal to 0: \(x=0\) - step11: Check if the solution is in the defined range: \(x=0,x \in \left[-5,0\right)\cup \left(0,5\right]\) - step12: Find the intersection: \(x \in \varnothing \) Solve the equation \( \frac{\sin(3x)}{\sin(5x)}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sin\left(3x\right)}{\sin\left(5x\right)}=0\) - step1: Find the domain: \(\frac{\sin\left(3x\right)}{\sin\left(5x\right)}=0,x\neq \frac{k\pi }{5},k \in \mathbb{Z}\) - step2: Cross multiply: \(\sin\left(3x\right)=\sin\left(5x\right)\times 0\) - step3: Simplify the equation: \(\sin\left(3x\right)=0\) - step4: Use the inverse trigonometric function: \(3x=\arcsin\left(0\right)\) - step5: Calculate: \(3x=0\) - step6: Add the period: \(3x=k\pi ,k \in \mathbb{Z}\) - step7: Solve the equation: \(x=\frac{k\pi }{3},k \in \mathbb{Z}\) - step8: Check if the solution is in the defined range: \(x=\frac{k\pi }{3},k \in \mathbb{Z},x\neq \frac{k\pi }{5},k \in \mathbb{Z}\) - step9: Find the intersection: \(x=\left\{ \begin{array}{l}\frac{\pi }{3}+k\pi \\\frac{2\pi }{3}+k\pi \end{array}\right.,k \in \mathbb{Z}\) Solve the equation \( \frac{5x^{2}+3x-1}{4x^{2}+5}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{5x^{2}+3x-1}{4x^{2}+5}=0\) - step1: Cross multiply: \(5x^{2}+3x-1=\left(4x^{2}+5\right)\times 0\) - step2: Simplify the equation: \(5x^{2}+3x-1=0\) - step3: Solve using the quadratic formula: \(x=\frac{-3\pm \sqrt{3^{2}-4\times 5\left(-1\right)}}{2\times 5}\) - step4: Simplify the expression: \(x=\frac{-3\pm \sqrt{3^{2}-4\times 5\left(-1\right)}}{10}\) - step5: Simplify the expression: \(x=\frac{-3\pm \sqrt{29}}{10}\) - step6: Separate into possible cases: \(\begin{align}&x=\frac{-3+\sqrt{29}}{10}\\&x=\frac{-3-\sqrt{29}}{10}\end{align}\) - step7: Rewrite the fraction: \(\begin{align}&x=\frac{-3+\sqrt{29}}{10}\\&x=-\frac{3+\sqrt{29}}{10}\end{align}\) - step8: Rewrite: \(x_{1}=-\frac{3+\sqrt{29}}{10},x_{2}=\frac{-3+\sqrt{29}}{10}\) Solve the equation \( \frac{\sin(5x)}{\tan(9x)}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sin\left(5x\right)}{\tan\left(9x\right)}=0\) - step1: Find the domain: \(\frac{\sin\left(5x\right)}{\tan\left(9x\right)}=0,x\neq \frac{k\pi }{18},k \in \mathbb{Z}\) - step2: Cross multiply: \(\sin\left(5x\right)=\tan\left(9x\right)\times 0\) - step3: Simplify the equation: \(\sin\left(5x\right)=0\) - step4: Use the inverse trigonometric function: \(5x=\arcsin\left(0\right)\) - step5: Calculate: \(5x=0\) - step6: Add the period: \(5x=k\pi ,k \in \mathbb{Z}\) - step7: Solve the equation: \(x=\frac{k\pi }{5},k \in \mathbb{Z}\) - step8: Check if the solution is in the defined range: \(x=\frac{k\pi }{5},k \in \mathbb{Z},x\neq \frac{k\pi }{18},k \in \mathbb{Z}\) - step9: Find the intersection: \(x=\left\{ \begin{array}{l}\frac{\pi }{5}+k\pi \\\frac{2\pi }{5}+k\pi \\\frac{3\pi }{5}+k\pi \\\frac{4\pi }{5}+k\pi \end{array}\right.,k \in \mathbb{Z}\) Solve the equation \( \frac{\sqrt(x+10)-4}{x-6}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sqrt{x+10}-4}{x-6}=0\) - step1: Find the domain: \(\frac{\sqrt{x+10}-4}{x-6}=0,x \in \left[-10,6\right)\cup \left(6,+\infty\right)\) - step2: Cross multiply: \(\sqrt{x+10}-4=\left(x-6\right)\times 0\) - step3: Simplify the equation: \(\sqrt{x+10}-4=0\) - step4: Move the constant to the right-hand side: \(\sqrt{x+10}=4\) - step5: Raise both sides to the \(2\)-th power\(:\) \(\left(\sqrt{x+10}\right)^{2}=4^{2}\) - step6: Evaluate the power: \(x+10=16\) - step7: Move the constant to the right side: \(x=16-10\) - step8: Subtract the numbers: \(x=6\) - step9: Check if the solution is in the defined range: \(x=6,x \in \left[-10,6\right)\cup \left(6,+\infty\right)\) - step10: Find the intersection: \(x \in \varnothing \) Solve the equation \( \frac{\sin(6x)}{4x}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sin\left(6x\right)}{4x}=0\) - step1: Find the domain: \(\frac{\sin\left(6x\right)}{4x}=0,x\neq 0\) - step2: Cross multiply: \(\sin\left(6x\right)=4x\times 0\) - step3: Simplify the equation: \(\sin\left(6x\right)=0\) - step4: Use the inverse trigonometric function: \(6x=\arcsin\left(0\right)\) - step5: Calculate: \(6x=0\) - step6: Add the period: \(6x=k\pi ,k \in \mathbb{Z}\) - step7: Solve the equation: \(x=\frac{k\pi }{6},k \in \mathbb{Z}\) - step8: Check if the solution is in the defined range: \(x=\frac{k\pi }{6},k \in \mathbb{Z},x\neq 0\) - step9: Find the intersection: \(x=\frac{k\pi }{6},k \in \left(-\infty,0\right),k \in \mathbb{Z}\cup k \in \left(0,+\infty\right),k \in \mathbb{Z}\) Solve the equation \( \frac{\sqrt(x+4)-3}{\sqrt(x-1)-2}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\sqrt{x+4}-3}{\sqrt{x-1}-2}=0\) - step1: Find the domain: \(\frac{\sqrt{x+4}-3}{\sqrt{x-1}-2}=0,x \in \left[1,5\right)\cup \left(5,+\infty\right)\) - step2: Cross multiply: \(\sqrt{x+4}-3=\left(\sqrt{x-1}-2\right)\times 0\) - step3: Simplify the equation: \(\sqrt{x+4}-3=0\) - step4: Move the constant to the right-hand side: \(\sqrt{x+4}=3\) - step5: Raise both sides to the \(2\)-th power\(:\) \(\left(\sqrt{x+4}\right)^{2}=3^{2}\) - step6: Evaluate the power: \(x+4=9\) - step7: Move the constant to the right side: \(x=9-4\) - step8: Subtract the numbers: \(x=5\) - step9: Check if the solution is in the defined range: \(x=5,x \in \left[1,5\right)\cup \left(5,+\infty\right)\) - step10: Find the intersection: \(x \in \varnothing \) Solve the equation \( 3x-12=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(3x-12=0\) - step1: Move the constant to the right side: \(3x=0+12\) - step2: Remove 0: \(3x=12\) - step3: Divide both sides: \(\frac{3x}{3}=\frac{12}{3}\) - step4: Divide the numbers: \(x=4\) Solve the equation \( \frac{\frac{1}{x}-\frac{1}{3}}{x^{2}-9}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\frac{1}{x}-\frac{1}{3}}{x^{2}-9}=0\) - step1: Divide the terms: \(-\frac{1}{3x\left(x+3\right)}=0\) - step2: Rewrite the expression: \(\frac{-1}{3x\left(x+3\right)}=0\) - step3: Cross multiply: \(-1=3x\left(x+3\right)\times 0\) - step4: Simplify the equation: \(-1=0\) - step5: The statement is false: \(x \in \varnothing \) Solve the equation \( \frac{\cos(x)-\frac{1}{2}}{x-\frac{\pi}{3}}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{\cos\left(x\right)-\frac{1}{2}}{x-\frac{\pi }{3}}=0\) - step1: Find the domain: \(\frac{\cos\left(x\right)-\frac{1}{2}}{x-\frac{\pi }{3}}=0,x\neq \frac{\pi }{3}\) - step2: Divide the terms: \(\frac{6\cos\left(x\right)-3}{2\left(3x-\pi \right)}=0\) - step3: Cross multiply: \(6\cos\left(x\right)-3=2\left(3x-\pi \right)\times 0\) - step4: Simplify the equation: \(6\cos\left(x\right)-3=0\) - step5: Move the constant to the right side: \(6\cos\left(x\right)=0+3\) - step6: Remove 0: \(6\cos\left(x\right)=3\) - step7: Divide both sides: \(\frac{6\cos\left(x\right)}{6}=\frac{3}{6}\) - step8: Divide the numbers: \(\cos\left(x\right)=\frac{1}{2}\) - step9: Use the inverse trigonometric function: \(x=\arccos\left(\frac{1}{2}\right)\) - step10: Calculate: \(\begin{align}&x=\frac{\pi }{3}\\&x=\frac{5\pi }{3}\end{align}\) - step11: Add the period: \(\begin{align}&x=\frac{\pi }{3}+2k\pi ,k \in \mathbb{Z}\\&x=\frac{5\pi }{3}+2k\pi ,k \in \mathbb{Z}\end{align}\) - step12: Find the union: \(x=\left\{ \begin{array}{l}\frac{\pi }{3}+2k\pi \\\frac{5\pi }{3}+2k\pi \end{array}\right.,k \in \mathbb{Z}\) - step13: Check if the solution is in the defined range: \(x=\left\{ \begin{array}{l}\frac{\pi }{3}+2k\pi \\\frac{5\pi }{3}+2k\pi \end{array}\right.,k \in \mathbb{Z},x\neq \frac{\pi }{3}\) - step14: Find the intersection: \(x=\left\{ \begin{array}{l}\frac{\pi }{3}+2k\pi ,k \in \left(-\infty,0\right),k \in \mathbb{Z}\cup k \in \left(0,+\infty\right),k \in \mathbb{Z}\\\frac{5\pi }{3}+2k\pi ,k \in \left(-\frac{2}{3},+\infty\right),k \in \mathbb{Z}\cup k \in \left(-\infty,-\frac{2}{3}\right),k \in \mathbb{Z}\end{array}\right.\) Let's evaluate the limits step by step using L'Hospital's Rule where applicable. ### 1. \( \lim _{x \rightarrow 4} \frac{3 x-12}{x^{2}-16} \) First, substitute \( x = 4 \): \[ \frac{3(4) - 12}{4^2 - 16} = \frac{0}{0} \] This is an indeterminate form, so we apply L'Hospital's Rule: \[ \lim_{x \to 4} \frac{3}{2x} = \frac{3}{2(4)} = \frac{3}{8} \] ### 2. \( \lim _{x \rightarrow -4} \frac{2 x^{2}+13 x+20}{x+4} \) Substituting \( x = -4 \): \[ \frac{2(-4)^2 + 13(-4) + 20}{-4 + 4} = \frac{32 - 52 + 20}{0} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to -4} \frac{4x + 13}{1} = 4(-4) + 13 = -16 + 13 = -3 \] ### 3. \( \lim _{x \rightarrow 6} \frac{\sqrt{x+10}-4}{x-6} \) Substituting \( x = 6 \): \[ \frac{\sqrt{6+10} - 4}{6-6} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 6} \frac{\frac{1}{2\sqrt{x+10}}}{1} = \frac{1}{2\sqrt{16}} = \frac{1}{8} \] ### 4. \( \lim _{x \rightarrow 0} \frac{\sin 6 x}{4 x} \) Substituting \( x = 0 \): \[ \frac{\sin(0)}{0} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 0} \frac{6\cos(6x)}{4} = \frac{6\cos(0)}{4} = \frac{6}{4} = \frac{3}{2} \] ### 5. \( \lim _{x \rightarrow 3} \frac{x^{2}-2 x-3}{x-3} \) Substituting \( x = 3 \): \[ \frac{3^2 - 2(3) - 3}{3-3} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 3} \frac{2x - 2}{1} = 2(3) - 2 = 6 - 2 = 4 \] ### 6. \( \lim _{x \rightarrow 0} \frac{\sqrt{25-x^{2}}-5}{x} \) Substituting \( x = 0 \): \[ \frac{\sqrt{25-0}-5}{0} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 0} \frac{-\frac{x}{\sqrt{25-x^2}}}{1} = -\frac{0}{5} = 0 \] ### 7. \( \lim _{x \rightarrow 0} \frac{\sin 3 x}{\sin 5 x} \) Substituting \( x = 0 \): \[ \frac{\sin(0)}{\sin(0)} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 0} \frac{3\cos(3x)}{5\cos(5x)} = \frac{3}{5} \] ### 8. \( \lim _{h \rightarrow 0} \frac{\sin (x+h)-\sin x}{h} \) This is the definition of the derivative of \( \sin x \): \[ \lim_{h \to 0} \frac{\sin (x+h)-\sin x}{h} = \cos x \] ### 9. \( \lim _{x \rightarrow \infty} \frac{5 x^{2}+3 x-1}{4 x^{2}+5} \) Dividing numerator and denominator by \( x^2 \): \[ \lim_{x \to \infty} \frac{5 + \frac{3}{x} - \frac{1}{x^2}}{4 + \frac{5}{x^2}} = \frac{5}{4} \] ### 10. \( \lim _{x \rightarrow 0} \frac{\sin ^{2} 2 x}{5 x^{2}} \) Substituting \( x = 0 \): \[ \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 0} \frac{2\sin(2x)\cdot 2\cos(2x)}{10x} = \frac{4\cdot 1}{10} = \frac{2}{5} \] ### 11. \( \lim _{x \rightarrow 0} \frac{\sin 5 x}{\tan 9 x} \) Substituting \( x = 0 \): \[ \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 0} \frac{5\cos(5x)}{9\sec^2(9x)} = \frac{5}{9} \] ### 12. \( \lim _{x \rightarrow 5} \frac{\sqrt{x+4}-3}{\sqrt{x-1}-2} \) Substituting \( x = 5 \): \[ \frac{\sqrt{5+4}-3}{\sqrt{5-1}-2} = \frac{3-3}{2-2} = \frac{0}{0} \] Applying L'Hospital's Rule: \[ \lim_{x \to 5} \frac{\frac{1}{2\sqrt{x+4}}}{\frac{1}{2\sqrt{x-1}}} = \frac{\sqrt{4}}{\sqrt{5}} = \frac{2}{\sqrt{5}} \] ### 13. \( \lim _{x \rightarrow \frac{\pi}{3}} \frac{\cos x-\frac{1}{2}}{x-\frac{\pi}{3}} \) Substituting \( x

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Absolutely! Let's dive into these limit evaluations with a dash of fun. 1. To find \( \lim _{x \rightarrow 4} \frac{3 x-12}{x^{2}-16} \), start by substituting \( x = 4 \): Both the numerator and denominator become zero (0/0 form). Apply L'Hôpital's Rule by taking the derivative of the numerator (3) and the denominator (2x), yielding \( \lim _{x \rightarrow 4} \frac{3}{8} = \frac{3}{8} \). 2. For \( \lim _{x \rightarrow -4} \frac{2 x^{2}+13 x+20}{x+4} \), plug in \( x = -4 \): You'll see that the denominator is zero and the numerator also evaluates to zero. Factor the numerator to get \( \frac{(2x+5)(x+4)}{x+4} \). Cancel the \((x + 4)\) and then evaluate, giving you \( \lim _{x \rightarrow -4} (2x + 5) = -3 \). 3. In solving \( \lim _{x \rightarrow 6} \frac{\sqrt{x+10}-4}{x-6} \), again, substitute \( x = 6 \) leads to \( 0/0 \). Multiply by the conjugate: \( \frac{\sqrt{x+10} + 4}{\sqrt{x+10} + 4} \). Simplifying reveals \( \lim _{x \rightarrow 6} \frac{x-6}{x + 14} = \frac{1}{20} \). 4. For \( \lim _{x \rightarrow 0} \frac{\sin 6 x}{4 x} \), knowing that \( \lim_{x \to 0} \frac{\sin kx}{kx} = 1 \), we rewrite as \( \frac{6}{4} \cdot \frac{\sin 6x}{6x} \) to get \( \frac{6}{4} = \frac{3}{2} \). 5. In \( \lim _{x \rightarrow 3} \frac{x^{2}-2 x-3}{x-3} \), substituting gives \( 0/0 \). Factor the numerator to \( (x - 3)(x + 1) \) and cancel \( (x - 3) \). The limit then evaluates directly to \( 4 \). 6. For \( \lim _{x \rightarrow 0} \frac{\sqrt{25-x^{2}}-5}{x} \), substituting gives \( 0/0 \). Multiply the numerator by the conjugate, leading to \( -\frac{x^2}{x(\sqrt{25-x^2}+5)} \), simplifying further gives \( -\frac{x}{5} \) leading to \( 0 \). 7. In \( \lim _{x \rightarrow 0} \frac{\sin 3 x}{\sin 5 x}\), rewrite using the limit of \( \frac{\sin kx}{kx} \) form yields \( \frac{3/5}{1} = \frac{3}{5} \). 8. For \( \lim _{h \rightarrow 0} \frac{\sin (x+h)-\sin x}{h} \), this is the definition of the derivative, yielding \( \cos x \) as \( h \to 0 \). 9. In \( \lim _{x \rightarrow \infty} \frac{5 x^{2}+3 x-1}{4 x^{2}+5} \), the leading terms dominate, giving \( \frac{5}{4} \) as \( x \to \infty \). 10. For \( \lim _{x \rightarrow 0} \frac{\sin ^{2} 2 x}{5 x^{2}} \), using \( \sin^2(kx) \sim k^2x^2 \), the limit approaches \( \frac{4}{5} \). 11. In \( \lim _{x \rightarrow 0} \frac{\sin 5 x}{\tan 9 x} \), rewrite with \( \tan 9x = \frac{\sin 9x}{\cos 9x} \) and simplify leads to \( \frac{5}{9} \). 12. For \( \lim _{x \rightarrow 5} \frac{\sqrt{x+4}-3}{\sqrt{x-1}-2} \), both the numerator and denominator evaluate to \( 0/0 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy